Traditional tattoo of the Croats inhabiting Bosnia and Herzegovina as a model of physical culture - Pac-Pomarnacka, Lidia Pac-Pomarnacka (Studia Etnologiczne i Antropologiczne, 2018)
Ornamental tattoo is a decorative element of the body of many cultures, often associated with a specific profession, for example a sailor, soldier, or with belonging to a given tribe, social group or subculture. The traditional tattoo of the Croats from the areas of Bosnia and Herzegovina was a manifestation, praise for certain ideals. It was part of the culture of the local Christian community. It was worn on the body as an indelible sign of religious affiliation and protection against Islamization. To this day, in many villages of Bosnia and Herzegovina it is possible to come across elderly women with traditional tattoos